Secure Distributed Programming with Value-Dependent Types - Swamy, Nikhil; Chen, Juan; Fournet, Cédric; Strub, Pierre-Yves; Bharagavan, Karthikeyan; Yang, Jean (2011)
Distributed applications are difficult to program reliably and securely. Dependently typed functional languages promise to prevent broad classes of errors and vulnerabilities, and to enable program verification to proceed side-by-side with development. However, as recursion, effects, and rich libraries are added, using types to reason about programs, specifications and proofs becomes challenging. We present F*, a full-fledged design and implementation of a new dependently typed language for secure distributed programming. Unlike prior languages, F* provides arbitrary recursion while maintaining a logically consistent core; it enables modular reasoning about state and other effects using affine types; and it supports proofs of refinement properties using a mixture of cryptographic evidence and logical proof terms. The key mechanism is a new kind system that tracks several sub-languages within F* and controls their interaction. F* subsumes two previous languages, F7 and Fine. We prove type soundness (with proofs partially mechanized in Coq) and logical consistency for F*. We have implemented a compiler that translates F* to .NET bytecode, based on a prototype for Fine. F* provides access to libraries for concurrency, networking, cryptography, and interoperability with C#, F# and the other .NET languages. The compiler produces verifiable binaries with 60% code size overhead for proofs and types, as much as a 45x improvement over the Fine compiler, while still enabling efficient bytecode verification. To date, we have programmed and verified more than 17,000 lines of F* including (1) new schemes for multi-party sessions; (2) a new zero-knowledge privacy-preserving payment protocol; (3) a provenance aware curated database; (4) a suite of 17 web-browser extensions verified for authorization properties; and (5) a cloud-hosted multi-tier web application with a verified reference monitor.
This is an extended version of the conference paper (ICFP '11) with the same title. A final version of this full technical report is forthcoming.